PEMBAGIAN KERjA DALAM RUMAH TANGGA (KASUS RUMAH TANGGA PEMULUNG DI KECAMATAN BANYUMANIK KOTA SEMARANG) (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Scavengers is one that becomes part of the recycling bin. Many scavengers do mobility to the location of potentially penghasilkan garbage. On the other hand be a new alternative employment opportunities due to limited employment opportunities. How scavenger involvement of women in decision-making within the household became one kajain in writing.The results can be seen that the division of household labor that are scavengers Nonproduction: housekeeping, child, and the surrounding residential neighborhood, still didominai by women. As for productive work: looking nahkah, still dominated by men. Women’s access to and control over resources is still low. no one has a home. All land ownership, on behalf of the husband. The advice can be given is still there needs to be empowerment for scavengers, as most people still have not received with open existence.Keywords: division of labor, Household, Scavengers, Recycling